Penggunaan Deiksis pada Novel "Perang" Karya Rama Wirawan - Tri Nita Rianti; Idawati; Asri Ismail (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to describe the forms of deixis namely personal deixis, spatial deixis, temporal deixis, discourse deixis, and social deixis used in the novel Perang by Rama Wirawan. This thesis is a literary study employing a pragmatic approach. The type of research used is qualitative, with the method applied being descriptive qualitative. The data collection techniques include reading, note-taking, and documentation. The data were analyzed through the stages of identification, classification, and description of words, phrases, or sentences containing deixis elements found in the novel. To ensure data validity, this study applies theory triangulation. The results of the study show that several types of deixis are found in the novel Perang by Rama Wirawan, namely personal deixis, spatial deixis, temporal deixis, discourse deixis, and social deixis. Personal deixis is the most dominant type because it illustrates the relationship between the speaker, the addressee, and a third party in the utterances. Meanwhile, spatial, temporal, discourse, and social deixis play important roles in constructing the unity of meaning, characters, setting, plot, and social relationships among the characters in the story.